2023
DOI: 10.3390/ph16020212
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatments and Natural Biocompounds in Weight Management

Abstract: The obesity pandemic is one of society’s most urgent public health concerns. One-third of the global adult population may fall under obese or overweight by 2025, suggesting a rising demand for medical care and an exorbitant cost of healthcare expenditure in the coming years. Generally, the treatment strategy for obese patients is largely patient-centric and needs dietary, behavioral, pharmacological, and sometimes even surgical interventions. Given that obesity cases are rising in adults and children and lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Studies in this direction aim to increase the concentration of cytokines involved in immune enhancement or boost the activity of immune cells that can directly kill cancer cells [ 28 , 29 ]. These natural substances have demonstrated the ability to non-specifically stimulate various immune cells, promoting overall body homeostasis and reducing the incidence of diseases [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this direction aim to increase the concentration of cytokines involved in immune enhancement or boost the activity of immune cells that can directly kill cancer cells [ 28 , 29 ]. These natural substances have demonstrated the ability to non-specifically stimulate various immune cells, promoting overall body homeostasis and reducing the incidence of diseases [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common side effects of combined naltrexone/bupropion treatment comprise gastrointestinal symptoms, seizures, palpitations, transient blood pressure increase, headache, insomnia and xerostomia. 110,113 The COR trials on the weight-reducing effect of naltrexone/bupropion in an obese population revealed a discontinuation rate varying between 11% and 18%. 108,115 The phentermine/topiramate combination also acts on the hypothalamus, reducing hunger and food intake [116][117][118] (Figure 5).…”
Section: First-generation Anti-obesity Drugsmentioning
confidence: 99%
“…108 The anticonvulsant topiramate promotes appetite suppression and increases satiety through gammaaminobutyric and glutamate agonism and carbonic anhydrase inhibition. 108,119,120 Because of an additive effect on weight loss, a fixed dose combination is approved for long-term weight loss 108,110 (Figure 5).…”
Section: First-generation Anti-obesity Drugsmentioning
confidence: 99%
“…In this context, research is now emphasizing the potential role of specific pharmacological management of obese patients [90,91]. In recent years, pharmacological molecules including orlistat, liraglutide, bupropion/naltrexone, cathin, phentermine/topiramate, and lorcaserin were integrated into the management of obesity and were pharmacological treatments approved by the FDA [90,91].…”
Section: Cancer Rehabilitationmentioning
confidence: 99%
“…In this context, research is now emphasizing the potential role of specific pharmacological management of obese patients [90,91]. In recent years, pharmacological molecules including orlistat, liraglutide, bupropion/naltrexone, cathin, phentermine/topiramate, and lorcaserin were integrated into the management of obesity and were pharmacological treatments approved by the FDA [90,91]. While growing interest has been reported in the pharmacological management of obese patients, it should be noted that a lifestyle approach combined with a specific nutritional intervention still remains the key component of obesity treatments.…”
Section: Cancer Rehabilitationmentioning
confidence: 99%